Expressions of shox2, RASSF1A and PTGER4, and the relationship between their methylation and clinicopathological characteristics in patients with lung cancer - Su Haitao; Lv Qiaoye; Wang Limei; Hu Jigang; Lv Yinggang; Jia Liting; Qi Qingbin (Journal of Medical Biochemistry)
Background: To explore the expressions of short stature homobox2 (SHOX2), Ras-association domain family 1A (RASSF1A) and prostaglandin E receptor 4 (PTGER4), and the relationship between their methylation and clinicopathological characteristics in patients with lung cancer (LC). Methods: The surgical specimens of cancer tissues and para-carcinoma tissues were collected from 50 patients with LC in the Affiliated Hospital of Hebei University of Engineering between January and November 2023. The expressions of SHOX, RASSF1A and PTGER4 proteins in cancer tissues and para-carcinoma tissues were detected by immunohistochemistry, and methylation status of SHOX, RASSF1A and PTGER4 genes in peripheral venous blood was detected by sulfite-modified real-time fluorescence quantification. The positive expression rates of SHOX2, RASSF1A and PTGER4, and positive rates of SHOX2, RASSF1A and PTGER4 genes methylation in cancer tissues and para-carcinoma tissues were compared. The relationship between SHOX2, RASSF1A, PTGER4 methylation and clinicopathological characteristics in LC patients was compared by real-time fluorescence quantitative PCR. Results: The positive expression rates of SHOX2, RASSF1A and PTGER4 in cancer tissues were 44.0%, 54.00% and 50.00%, significantly lower than those in para-carcinoma tissues (90.00%, 96.00%, 82.00%, P<0.05). The methylation positive rates of SHOX2, RASSF1A and PTGER4 genes in cancer tissues were 48.00%, 32.00% and 64.00%, significantly higher than those in para-carcinoma tissues (16.00%, 4.0%, 14.00%, P<0.05). In terms of different pathological types and TNM staging, methylation positive rates of SHOX2 and RASSF1A genes were the highest in patients with adenocarcinoma and TNM staging at stage IV. However, since the study included a limited sample size and only two major histological subtypes of LC, caution is needed in generalizing these findings across all stages and types of LC. Larger, more diverse studies are needed to determine if these findings can be broadly applied to other LC subtypes and stages. In terms of different pathological types, methylation positive rate of PTGER4 gene was the highest in patients with TNM staging at stage IV (P<0.05). While these results indicate a correlation between PTGER4 methylation and advanced disease stage, further research with a larger, more heterogeneous patient population is necessary to validate whether these findings hold true across all stages and histological subtypes of LC. Conclusions: The low expressions and high methylation of SHOX2, RASSF1A and PTGER4 are common in LC patients. However, it is important to note that the small sample size and the cross-sectional nature of this study limit the ability to generalize these findings to a broader population. Additionally, the lack of longitudinal data means we cannot assess how methylation changes over time or in response to treatment, which is a significant limitation. The methylation positive rates of SHOX2 and RASSF1A genes are related to pathological types and TNM staging, and methylation positive rate of PTGER4 gene is only related to pathological types. These findings suggest that SHOX2, RASSF1A, and PTGER4 gene methylation could be valuable biomarkers for the early detection of LC, particularly in high-risk populations or those with atypical presentations. However, further studies with larger sample sizes and longitudinal designs are needed to confirm these findings and evaluate the long-term clinical utility of these methylation markers in monitoring disease progression and treatment response.